Why Triangular Development Cooperation? Germany and the Emerging Powers. Issue 1 (2nd January 2016) - Lengfelder, Christina Sandra
Abstract : Triangular development cooperation (TriCo) is a relatively new form of technical cooperation (expert advice), which includes, besides the traditional actors of the donor and the receiver, a third country: the new provider. At first sight, OECD donors' engagement in TriCo cannot be explained by any of the traditional explanations for aid provision. On the one hand, donors pass on their strategically favourable position to the new providers, whereas on the other hand, from a practitioners' view, TriCo is not necessarily beneficial for receiving countries. Therefore, donors' participation in TriCo constitutes a stunning puzzle of international politics. An in-depth case study assesses why Germany has recently engaged in TriCo. Exploring this empirical riddle does not only contribute to understanding this specific cooperation modality, but it also reveals insights for the general study of international cooperation: emerging powers are changing the landscape of international relations.